Cultura política conservadora na produção intelectual de Lúcio José dos Santos : A Inconfidência Mineira (1927) e Philosophia, Pedagogia, Religião (1936) - Gama, Luciana Coelho (2022)
This research aims to analyze the conservative political culture of the Catholic intellectual Lúcio José dos Santos (18751944), through the books A Inconfidência Mineira (1927) e Philosophia, Pedagogia, Religião (1936). Born in Minas Gerais, Santos stood out nationally as a historian and educator, with the books cited as his main productions in these areas. The question to be answered in the research is: being Santos a conservative, how does this political culture manifest itself in his main works? This research is justified by the relevant intellectual and political performance of this subject and by the repercussion of his works, which were little analyzed later and, according to the hypothesis of this thesis, have conservatism as a common and structuring point, since Lúcio José dos Santos defended ideas such as exaltation of the past, defense of traditions, cult of the country and heroism, defense of Catholic pedagogy and religious teaching in schools, anticommunism and antiliberalism etc. The methodology used will be the analysis of the texts of the sources, divided into categories according to the subthemes that the author addresses, identifying how the essential aspects of Santos’ political culture are evident in his conceptions of History and Education. For that, the works of JeanFrançois Sirinelli will be used as theoretical references, to understand Santos as an intellectual, Karl Mannheim, to define conservatism, and Serge Berstein and Rodrigo Patto Sá Motta, to conceptualize political culture and apply this concept to the source investigation.